Path dependence in technologies and organizations: A concise guide - Carolina Castaldi; Giovanni Dosi; Evita Paraskevopoulou (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2011)
The note on which an entry for the Palgrave Encyclopedia of Strategic Management will draw offers a beginner's guide to path dependency in technologies and organizations. We address the very meaning of the concept and its centrality in various aspects of economic analysis. We outline the various levels of the ecomic system in which it is observable, its sources, concequences and different formal representations of path dependent processes.
Keywords: 330; path dependence; lock-in; dynamic increasing returns; organizational inertia